การให้ความสำคัญต่อมุมมองตามแนวคิดระบบการวัดผลการปฏิบัติงานดุลยภาพและความสัมพันธ์ต่อผลการดำเนินงานขององค์กรในอุตสาหกรรมนมพร้อมดื่มของประเทศไทย - วรรณพร ปิติพัฒนะโฆษิต (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The objectives of this study are threefold (1) to study the perceived importance of balance scorecard perspectives: financial, customer, internal process, innovation & learning, social, and environment; (2) to study the key performance indicators in the drinking milk industry in Thailand; and (3) to study the relationship between the perceived importance of balance scorecard perspectives and organizational performances. The study framework was developed from the balance score card theory. A self-administered questionnaire was sent to the management in the highest position of the firms of Thailand drinking milk industry. The response rate was 54.02 percent. The methods of analysis and model testing included the exploratory factor analysis and the Linear Structural Relationship (LISREL). The results showed that perceived importance can be grouped into 3 areas: (1) sales-profit and market share; (2) customer, internal process, and financial efficiency; and (3) innovation, social, and environment. The firms in Thai drinking milk industry rated the customer, internal process, and financial efficiency area and the innovation, social and environment area as being more important than the sales-profit and market share. The two organizational performances, financial and non-financial, were found to have some causal relationships to the perceived importance. While the non-financial performance measures were rated as being more important than the financial ones, the former was also found to link to perceived importance of the sales profit and market share area whereas the latter was found to link to the innovation, social and environment area. No causal link was found between either the financial and non-financial performances and the perceived importance in the area of customer, internal process, and financial efficiency.